Towards a professional civil service in post-transition Romania - Lee, Charlotte (2009)
To what degree and under what conditions can a young democracy build a competent, politically neutral public bureaucracy? A crucial component of the transition from communist party rule to democracy is the creation of a professional civil service. Success along this dimension of state-building generates administrative capacity: non-elected public officials ensure the implementation of reforms initiated by political leaders. In the communist party-led regimes of Eastern Europe, forging this new administrative class from its highly politicised predecessor took place as new democracies sought to overcome historical legacies and integrate with the European Union. A case study of administrative reform in Romania during the post-1989 period suggests the importance of external influences in forming a civil service more closely adhering to the Weberian ideal of an expert, rules-based bureaucracy. Through analysis of survey data from a nationally representative sample of the Romanian civil servants, the public bureaucracy has professionalised insofar as educational and training credentials rather than political affiliation are significant predictors of salary levels. - Reproduced.
Keywords: Civil service